2018
DOI: 10.3126/jiaas.v35i1.22520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Fungicides Against Fusarium oxysporum f. sp. lentis in Vitro at Lamjung, Nepal

Abstract: Fusarium is a soil borne pathogen which is common in almost all types of soil causing heavy losses in the crop production. Long term survival of pathogen in the soil as chlamydospores has increased its threat making it a highly devastating disease. High accessibility and simple application process of chemical control method has made it an effective and highly adopted approach of eliminating disease causing organisms. The present study was conducted in IAAS, Lamjung Campus to test the efficacy of fungicides in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
4
8
0
1
Order By: Relevance
“…It was observed that inhibition of the pathogen growth also increased with increasing concentration of all fungicides which are in complete agreement with those of Dahal et al 41 In the current research, carbendazim was found to be the most potent chemical in all concentration against the wilt pathogen as it almost totally inhibited the fungus mycelium growth. This result was in congruent with the findings of Patil et al, 42 Maheshwari et al, 43 Srivastava et al 44 and Dahal et al 41 Khanzada et al 45 and Narayanan et al 46 who found complete inhibition of F. oxysporum by carbendazim. Rajput et al 27 reported best result with carbendazim to reduce the mycelial growth of F. oxysporum f. sp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was observed that inhibition of the pathogen growth also increased with increasing concentration of all fungicides which are in complete agreement with those of Dahal et al 41 In the current research, carbendazim was found to be the most potent chemical in all concentration against the wilt pathogen as it almost totally inhibited the fungus mycelium growth. This result was in congruent with the findings of Patil et al, 42 Maheshwari et al, 43 Srivastava et al 44 and Dahal et al 41 Khanzada et al 45 and Narayanan et al 46 who found complete inhibition of F. oxysporum by carbendazim. Rajput et al 27 reported best result with carbendazim to reduce the mycelial growth of F. oxysporum f. sp.…”
Section: Discussionsupporting
confidence: 91%
“…There was a positive association between concentration and inhibition of the pathogen growth. It was observed that inhibition of the pathogen growth also increased with increasing concentration of all fungicides which are in complete agreement with those of Dahal et al 41 …”
Section: Discussionsupporting
confidence: 91%
“…Variations in sensitivity against fungicides in different Fusarium spp. and isolates have also been reported by Rajput et al, 2006;Amini et al, 2010;Andrabi et al, 2011;Maitlo et al, 2014;Dahal and Shrestha 2018.…”
Section: Sensitivity To Fungicidessupporting
confidence: 60%
“…To maintain the level of faba bean yield both quantitatively and qualitatively, farmers often rely heavily on the use of chemical fungicides to control the disease [ 11 ]. Conversely, the application of chemical fungicides in faba bean growing field results in the development of resistance by the plant pathogens, hazardous to human health, pollute the environment and harm biodiversity of the ecosystem [ 12 ].…”
Section: Introductionmentioning
confidence: 99%